A dispersion study of the aerosol emitted by fertiliser plants in the region of Serra do Mar Sierra, Cubatao, Brazil. (1st January 2001) - Kerr, A.F.S.; Anfossi, D.; Carvalho, J. da Costa; Castelli, S. Trini
The dispersions of inhalable particulate matter emitted by the fertiliser plants at Cubatao (Brazil) were simulated using the Lagrangian dispersion model SPRAY. Wind fields and other meteorological variables were obtained with the model RAMS. The results of these simulations were compared with the source apportionment performed by chemical mass balance on samples of the local aerosol.